3D printing of PLA/n-HA composite scaffolds with customized mechanical properties and biological functions for bone tissue engineering. (1st November 2021) - Wang, Wenzhao; Zhang, Boqing; Li, Mingxin; Li, Jun; Zhang, Chengyun; Han, Yanlong; Wang, Li; Wang, Kefeng; Zhou, Changchun; Liu, Lei; Fan, Yujiang; Zhang, Xingdong
Abstract: Bone defect caused by trauma, tumor, infection, and other reasons is a thorny problem that needs to be solved in orthopedic clinic. Customized bone repair biomaterials and their fabrication still need to be explored. Three-dimensional (3D) printing is a high-speed fabrication process for bone tissue biomaterials, which paves the way of solving clinical bone defect problems in a new way. In this study, the fused deposition modeling (FDM) technology was used to prepare the composite scaffolds of polylactic acid (PLA) and nano-hydroxyapatite (n-HA). The composite scaffold was optimized by material characterization, mechanical property test, and in vitro bone marrow mesenchymal stem cells biocompatibility test. Finally, a rabbit model was established to evaluate the osteogenic ability of PLA/n-HA scaffolds in vivo . The results showed that the PLA/n-HA composites proposed in this study were highly printable, and the printed scaffold showed tunable mechanical strength accompanied by the proportion of n-HA components. The biocompatibility and osteogenic induction properties were proved better than that of the pure PLA scaffold. This composite scaffold of PLA and n-HA provides a promising strategy for the repair of large bone defects.